Programul „Școală după școală: un sprijin necesar pentru elevii de etnie romă și turcă din județul Constanța - Mărginean, Ioan; Neagu, Gabriela; Mihalache, Flavius; Vasile, Marian (Calitatea Vieții, 2011)
The objective of this approach is to present and analyze the results of the research conducted in eight schools from five cities. In the project “A necessary support for Rroma and Turkish students in Constanţa County” we analyzed the profile of the schools included in the research, the cases of success in avoiding school dropout and the cases of school dropout. Our final goal was to advance a guide of good practices for prevention and reducing school dropout. Some results of the research demonstrate that fact is possible.